The Implementation of Affective Evaluation in Elementary School Curriculum in Padang, West Sumatra Province, Indonesia - Bentri, Alwen; ., . (International Journal of Engineering and Technology, 2018)
Evaluation is an important aspect in learning process. There are three aspects evaluated in learning process, namely: cognitive, affective, and psychomotor aspects. Evaluating psychomotor aspects has put elementary school teachers in difficulty due to too many aspects to be covered in the evaluation instrument which has caused impossibility to fully implement them. This condition has been made worse by the poor understanding of some teachers on the implementation of the affective evaluation. This study explored the implementation of affective evaluation in elementary schools in Padang, West Sumatra, Indonesia.Â  It was descriptive-quantitative in nature the population of the study were all the elementary schools having implemented affective evaluation in the city. The sample size was 112 teachers taken from 9 (nine) model schools. Questionnaire was used to collect data and the collected data were then analyzed descriptively and displayed in diagrams. The result of the analysis showed that the implementation of affective evaluation instruments which covered: preparation, administration, and the analysis of the score by the elementary school teachers was categorized GOOD, this was supported by the facts that all aspects of the instruments of the competence had already been covered although but not yet optimal, some improvement should be done.Â Â